Rheological Characterization of Isabgol Husk, Gum Katira Hydrocolloids, and Their Blends - Vipin Kumar Sharma; Bhaskar Mazumder; Vinod Nautiyal (International Journal of Food Science)
The rheological parameters of Isabgol husk, gum katira, and their blends were determined in different media such as distilled water, 0.1 N HCl, and phosphate buffer (pH 7.4). The blend properties of Isabgol husk and gum katira were measured for four different percentage compositions in order to understand their compatibility in dispersion form such as 00 : 100, 25 : 50, 50 : 50, 75 : 25, and 100 : 00 in the gel strength of 1 mass%. The miscibility of blends was determined by calculating Isabgol husk-gum katira interaction parameters by Krigbaum and Wall equation. Other rheological properties were analyzed by Bingham, Power, Casson, Casson chocolate, and IPC paste analysis. The study revealed that the power flow index “p” was less than “1” in all concentrations of Isabgol husk, gum katira, and their blends dispersions indicating the shear-thinning (pseudoplastic) behavior. All blends followed pseudoplastic behavior at thermal conditions as 298.15, 313.15, and 333.15°K and in dispersion media such as distilled water, 0.1 N HCl, and phosphate buffer (pH 7.4). Moreover, the study indicated the applicability of these blends in the development of drug delivery systems and in industries, for example, ice-cream, paste, nutraceutical, and so forth.